O niilismo e seu processo histórico no pensamento europeu, através do pensamento de Nietzsche. - Oliveira, Hallan Pereira de (2013)
The following work constitutes a reflection about the concept of nihilism and its progress of development in the European thought through the philosophy of Nietzsche. This reflection is the result of a research that relates Nietzsche s works with some of his interpreters. The study begins with the genealogic analyses of the ascetic ideals, for which the philosopher shows as expressions of the three types of nihilism (passive, reactive, and active) that emerges in this development process in Europe, process through which the nihilism becomes effective. The adopted methodology was to develop a vertical and horizontal study in the works of Nietzsche, study that articulated with that of his interpreters, resulted in the affirmation that perhaps this is Nietzsche s main objective in diagnosing this man s disease: that the nihilism is the cause of all diseases in the man s life, in the sense of leading him to self-destruction. Nietzsche s attempt in this case would be to show another direction, teaching, pointing the way to a bridge of superation of all values the Übermensch (superman) being this only way to engage a combat against all nihilist value, seeking always the perspective of life affirmation in its becoming, seeking his meaning in himself and in the Earth.